Asymmetries in international merchandise trade statistics: A case study of selected countries in Asia and the Pacific - Marko Javorsek (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2016)
This working paper introduces the concept of bilateral asymmetries in international merchandise trade statistics (IMTS), i.e. the discrepancies that can be seen in reported bilateral trade flows between trading partners. Such discrepancies mean that the value of exports reported by one country does not equal the value of imports reported by its partner, also called mirror data. These discrepancies impact bilateral trade balances and other economic variables reliant upon trade balance and thus are relevant from trade and economic policymaking. Asymmetries in bilateral trade statistics are a serious concern for the quality of statistics, especially from the perspective of consistency. They may also lead to misconceptions about trade balances among policy-makers, businesses and the general public. This paper provides an overview of the main concepts in IMTS and defines asymmetries in bilateral trade statistics. It outlines how to measure the discrepancies in bilateral trade statistics and provides a case study for 10 countries in Asia and the Pacific. The paper also provides an overview of the sources of bilateral trade asymmetries and suggests some basic actions that can be taken to improve the quality of IMTS and reduce bilateral asymmetries, or at least, allow researchers to balance bilateral trade flows for analytical purposes.
Keywords: C82; F13; F14; F15; F23; O19; O24; 330; international merchandise trade statistics; bilateral trade asymmetries; trade balance; valuation; discrepancies in mirror trade data; Asia and the Pacific